Full suspension mountain bike improves off-road cycling performance - Nishii, T.; Umemura, Y.; Kitagawa, K. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purpose of the present study was to determine the effects of suspension systems on the cycling performance of cyclists during off-road bicycling. METHODS: Eight elite male cyclists (67.8+/-5.8 ml/min/kg of (.-)VO(2max)) performed 30-minute riding tests on bicycles with 2 different suspension setups: front suspension (FS) and front and rear suspension (FRS). Heart rate, blood lactate concentration, pedaling power, cadence, cycling velocity, and completed distance during the trial were measured creatin kinase (CK), lactic dehydrogenase (LDH) and glutamic-oxaloacetic transaminase (GOT) were measured before and after the trials. RESULTS: The average cadence during the trial was significantly higher (p<0.05) with the FRS (73.6+/-6.1 rpm) than the FS (70.2+/-6.2 rpm). Subjects rode significantly faster (p<0.05) on FRS (24.1+/-2.6 km/h) than FS bikes (22.9+/-2.4 km/h), although no significant difference was observed in pedaling power (240.7+/-26.6 W vs 242.2+/-28.8 W, FS vs FRS, respectively). Serum creatin kinase increased significantly (p<0.05) at 24 h after the trial when cyclists exercised with the FS bike. CONCLUSIONS: We conclude that the FRS improved cycling performance over rough terrain. FRS might therefore be more suitable for cross-country mountain bike races.